PENGEMBANGAN MEDIA SCRAPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI KERAGAMAN BUDAYA SISWA KELAS IV SD - Rezza Sari Febriani; Fitria Dwi Prasetyaningtyas (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The use of ineffective learning media that is not suited to student characteristics has resulted in low student learning outcomes in the subject of Indonesian Cultural Diversity in IPAS (Integrated Science and Mathematics) lessons. The purpose of this study was to develop scrapbook learning media and analyse its feasibility and effectiveness in improving the learning outcomes of Grade IV students at Podorejo 01 State Elementary School in Semarang City. The research used the Research and Development (R&D) method with the Borg and Gall model, which was carried out up to the product testing stage. The research subjects consisted of 24 fourth-grade students who were divided into two testing stages, namely small-scale testing and large-scale testing. Data collection techniques consisted of observation, interviews, pretest–posttest, validation questionnaires, and response questionnaires. The validation results showed that the scrapbook media was deemed very feasible, with a percentage of 97% from media experts and 87.5% from subject matter experts. The effectiveness test results showed that student learning outcomes had improved. In the small-scale trial, the average score increased from 71.3 to 81.3, while in the large-scale trial, it increased from 61.5 to 88.6. Statistical analysis using the paired samples t-test and Wilcoxon signed-rank test showed a statistically significant difference in learning outcomes (p < 0.05). The N-Gain calculation results obtained a value of 0.67 in a small-scale trial with a moderate category and 0.89 in a large-scale trial with a high category. Thus, scrapbook learning media is declared feasible and effective for use in IPAS learning in Grade IV of elementary school. ABSTRAK Pemanfaatan media pembelajaran yang tidak efektif dan tidak sesuai dengan karakteristik siswa menyebabkan hasil belajar siswa rendah pada materi Keragaman Budaya Indonesia dalam pembelajaran IPAS. Tujuan dari penelitian ini untuk mengembangkan media pembelajaran scrapbook serta menganalisis kelayakan dan keefektifannya dalam meningkatkan hasil belajar siswa kelas IV SD Negeri Podorejo 01 Kota Semarang. Penelitian menggunakan metode Research and Development (R&D) dengan model Borg and Gall yang dilaksanakan sampai pada tahap uji coba produk. Subjek penelitian berjumlah 24 siswa kelas IV yang dibagi ke dalam dua tahap uji coba, yakni uji coba skala kecil dan uji coba skala besar. Teknik pengumpulan data terdiri atas observasi, wawancara, tes pretest–posttest, angket validasi, dan angket tanggapan. Hasil validasi memperlihatkan bahwa media scrapbook dinyatakan sangat layak dengan persentase 97% dari ahli media dan 87,5% dari ahli materi. Hasil uji keefektifan menunjukkan bahwa hasil belajar siswa mengalami peningkatan. Pada uji coba skala kecil, nilai rata-rata meningkat dari 71,3 menjadi 81,3, sedangkan pada uji coba skala besar meningkat dari 61,5 menjadi 88,6. Analisis statistik menggunakan uji paired samples t-test dan uji Wilcoxon signed-rank test menunjukkan adanya perbedaan hasil belajar yang signifikan secara statistik (p < 0,05). Hasil perhitungan N-Gain memperoleh nilai 0,67 pada uji coba skala kecil dengan kategori sedang dan 0,89 pada uji coba skala besar dengan kategori tinggi. Dengan demikian, media pembelajaran scrapbook dinyatakan layak dan efektif digunakan dalam pembelajaran IPAS kelas IV sekolah dasar.